Pan-cancer analysis reveals TRA16 as a master regulator of human carcinogenesis - Zhu, Yanyan; Gao, Yike; Huang, Xiaoqing; Chen, Bowang; Wang, Xinyi; Wu, Ying; Sun, Jian; Huang, Xiaoyun (Frontiers in Oncology, 2025)
IntroductionThe nuclear receptor TR4 binding protein, TRA16, has been implicated in lung carcinogenesis; however, its broader role across diverse human cancers remains poorly understood. Understanding TRA16’s involvement in cancer biology could uncover novel regulatory mechanisms and potential therapeutic targets.MethodsWe conducted a comprehensive pan-cancer analysis of TRA16 expression and function across multiple human malignancies. Gene co-expression networks, pathway enrichment, transcription factor analysis, organoid modeling, and intercellular communication profiling were employed. Tumor mutation burden (TMB) and microenvironmental features were also assessed in relation to TRA16 expression, stratified by TP53 mutation status.ResultsCorrelation analysis identified the cell cycle as the top enriched pathway among TRA16-associated genes, with key transcription factors, including RB-E2F, MYC, and TP53, regulating genes co-expressed with TRA16. In liver cancer organoid models, TRA16 and its co-expressed genes were significantly upregulated. Intercellular communication analysis showed that TRA16-positive cells exhibited increased autocrine signaling and overall signaling activity. Importantly, patients with high TRA16 expression demonstrated elevated TMB and decreased stromal and immune features.DiscussionThese findings highlight TRA16 as a potential master regulator of oncogenic processes, contributing to tumor progression through coordinated regulation of cell cycle genes, intercellular signaling, and genomic instability. Our results provide new insights into TRA16’s role across cancers and support its potential as a novel oncogene.